Impact and legacy of the Matsanga movement on the Eastern Highlands of Zimbabwe: a case study of Chipinge district 1976-1992 - Mukonza, Pauline (Midlands State University, 2017)
This study seeks to establish the impact and legacy of the RENAMO war on Chipinge District which is located in the Eastern Highlands of Zimbabwe. The issue of landmines scattered around the area, boarded issues as well as the increasing number of refugees and refugee camps in Chipinge prompted this study. The research has looked at the incursions of the Matsanga into Chipinge and their impact on the area which include attack on infrastructure, property and the people. Memories of RENAMO activities amongst the women and children were also looked at and these include psychological trauma, sexual assaults, conscription into the army as child soldiers as well as mutilations. Legacies of the Renamo war was also documented in this research, they include landmines, disabled people, and damaged infrastructure.In coming up with this research, interviews, archival sources and secondary sources were consulted